A novel nanoporous silicon prepared using electrochemical deposition technique for light emitting diode applications - Abdullah, Saifollah; Rusop, Mohamad; Muhamad, Muhamad Rasat (World Scientific Publishing, 2006)
The electroluminescence (EL) studies on the aluminum-doped nanoporous silicon (NPSi:Al) have been conducted. Nanoporous silicon (NPSi) layers have been prepared by anodically etching the unpolished p-type Si[100] wafer with surface resistivity of 4-8 Ωcm-1 in hydrofluoric solution at 1:1 ratio of ethanol. Aluminum (Al) was doped on NPSi using cathodic electrodeposition composed of aluminum chloride (AlCl3) and ethanol electrolyte. A diode structure has been fabricated comprising a semi-transparent Au/NPSi:Al/p-Si/Al ohmic contact electrode showing rectification on a forward bias I-V curve. EL from NPSi and NPSi:Al/p-Si has also been observed using the diode structure. The NPSi:Al/p-Si device shows increasing EL quantum efficiency at about 30%, and blue-shift EL spectra are observed. Possible reasons for the enhancement will be discussed. © World Scientific Publishing Company.